Analisis Aliran Air Tanah Akibat Penyekatan Kanal Di Lahan Gambut - Frans Alfredo Hutapea; Rinaldi Rinaldi; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Peat restoration measures are needed to rehabilitate peat ecosystems. The Peat Restoration Agency (BRG) has implemented peat restoration efforts one of them through rewetting activities within the territory of the Peat Hydrological Unity (KHG). The village of Lukun has burnt and degraded peatlands. With the rewetting of the peat, it is expected that the hydrologically disturbed peat will be improved and the peat will remain in wet conditions so that the degradation rate and potential of peat fires can be prevented. Therefore, the analysis of the peatlands wetting area due to the construction of canal blocking using the water level logger was set up in several dipwells around the canal bloking area. The results of water level logger give a reading in the form of hydrostatic pressure and atmospheric pressure then processed into graphs of groundwater fluctuations.This research showed the results that canal blocking has an impact on ground water level fluctuations as an effort to wet peatlands and the wetting radius that results from canal blocking is less than 100 meters. Besides the canal blocking, the increase in groundwater level is also influenced by rainfall. Keywords: water level logger, groundwater level, canal blocking, peat land wetting.